2022
DOI: 10.1021/acsnano.2c03051
|View full text |Cite
|
Sign up to set email alerts
|

Photodetection and Infrared Imaging Based on Cd3As2 Epitaxial Vertical Heterostructures

Abstract: Due to the nontrivial electronic structure, Cd3As2 is predicted to possess various transport properties and outstanding photoresponses. Photodetectors based on topological materials are mostly made up of nanoplates, yet monolithic in situ heteroepitaxial Cd3As2 photodetectors are rarely reported to date owing to the crystal mismatch between Cd3As2 and semiconductors. Here, we demonstrate Cd3As2/Zn x Cd1–x Te/GaSb vertical heteroepitaxial photodetectors via molecule beam epitaxy. By constructing dual-Schottky j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Moreover, the R was significantly improved to 729 mA W À1 . In 2022, Yang et al 97 realized the light response from the visible to the infrared band by constructing a double heterojunction. They prepared a wideband photodetector with Cd 3 As 2 / Zn x Cd 1Àx Te/GaSb vertical heterostructure through simple and controllable magnetron sputtering and photolithography technology.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…Moreover, the R was significantly improved to 729 mA W À1 . In 2022, Yang et al 97 realized the light response from the visible to the infrared band by constructing a double heterojunction. They prepared a wideband photodetector with Cd 3 As 2 / Zn x Cd 1Àx Te/GaSb vertical heterostructure through simple and controllable magnetron sputtering and photolithography technology.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…In addition, our previous work has shown that the photoexcited carrier relaxation time (a few picoseconds) in Cd 3 As 2 films gradually increases with temperature [59,64]. And the carrier density is known to increase with temperature as well [58,65]. Therefore, under the same excitation pump power, the higher-density carriers will be excited at the elevated temperature, though the electron mobility decreases with increasing temperature.…”
Section: Sample Undoped Sample-a Sample-b Sample-c Eectron Density (Cmmentioning
confidence: 99%
“…[1][2][3][4][5][6] Traditional photodetectors are usually composed of semiconductor nanostructures owing to their high light absorption coefficients and tunable band gaps. [7][8][9][10] However, the preparation process of those photodetectors often requires a complex material growth process and a high-cost integrated procedure. 11 Currently, colloidal nanocrystal-based photodetectors have achieved significant development because of their outstanding advantages, such as a simple preparation process, large optical absorption cross sections and good compatibility with many kinds of substrates for device fabrication.…”
Section: Introductionmentioning
confidence: 99%